Primary care and specialist physicians’ prescribing preferences for concurrent probiotic-antibiotic therapy: a multinational clinical practice survey across 13 countries - Vavricka, Stephan R.; Bartoli, Cecilia; Castillo, Carolina (Frontiers in Medicine, 2025)
Antibiotic-induced intestinal microbiota disruption represents a significant clinical concern, yet physician practices regarding concurrent probiotic supplementation remain poorly characterized across international healthcare systems. We investigated physician attitudes, knowledge, and prescribing behaviors in 390 physicians from 13 countries concerning probiotic-antibiotic co-administration and evaluated receptivity to innovative probiotic formulations with a cross-sectional online survey conducted in June 2025. Sampling included random selection of direct email outreach to known internal medicine specialists, general practitioners, and family physicians. Participants included internal medicine specialists (42%), general practitioners (46%), and family physicians (12%). There was an overall response rate of 52%. While 98% of physicians demonstrated high awareness of antibiotic-induced microbiota disruption, only 37% consistently recommended probiotics when prescribing antibiotics, with substantial variation in co-prescribing practices: 7% prescribed probiotics to nearly all patients, 13% to 1–10, 20% to 11–25, 33% to 26–50, and 27% to 51–99% of antibiotic recipients. Regional variations showed Lithuania, Colombia and Peru had the highest co-prescription rates (50% of physicians prescribing to >50% of patients), while Finland demonstrated more conservative patterns (50% prescribing to <25% of patients). During cold and flu season, antibiotic prescribing rates were evenly distributed across physician groups but decreased substantially outside peak respiratory illness periods. Most physicians (68%) found probiotics useful when taken with antibiotics, with 96% considering them for patients with prior antibiotic-associated diarrhea history. Physician receptivity to advanced probiotic formulations was consistently high, with 92% welcoming products that could be taken simultaneously with antibiotics and 92% willing to recommend such products to patients with special concerns, indicating that while physicians maintain high awareness of antibiotic microbiome impact, probiotic co-prescribing practices remain inconsistent globally with regional variations reflecting differences in healthcare policies and clinical guidelines.